Diagnostic Evaluation of Doshaja Kasa w.s.r to Hematological Investigations (AYUSHDHARA, 2021)
Kasa is one of the commonest complaints in day to day life and clinical manifestation affecting Pranavaha Srotas. Among the five major types of Kasa mentioned by Acharyas, Vata, Pitta & Kaphaja Kasa have distinct and significant clinical features and Samprapti. Early intervention is necessary in case of Kasa as it is a potential Nidanarthakara Vyadhi (disease having tendency to produce secondary diseases) to produce Kshaya. This observational study involving 150 subjects of age group 16 to 60 was carried out to assess the utility of hematological investigations (T.C, D.C, AEC, and ESR) to diagnose Vata, Pitta and Kaphaja Kasa respectively. Assessment of type of Kasa was done by scoring system of classical symptoms and changes in laboratory parameters were noted for each. Results are drawn based on Statistical evaluation of each type of Kasa with respect to each of the hematological investigation involved in the study. Investigations like neutrophil count, absolute eosinophil count and lymphocyte count have shown significant association with respect to Vataja, Pittaja and Kaphaja Kasa.